Knowledge and Attitudes of Tahirah Al Baeti Bulukumba Midwifery Academy Students About HIV and AIDS - Jusni Jusni; Mudyawati Kamaruddin; Rina Mariana (Sorume Health Sciences Journal, 2020)
HIV (Human Immunodeficiency Virus) is a virus that can cause AIDS by attacking white blood cells so that it can damage the human immune system. The cause of death in people with HIV and AIDS (PLWHA) is a progressive decline in the immune system so that opportunistic infections (OIs) can appear and end in death. Most teenagers still do not understand how the impact that will be caused by promiscuity among adolescents is happening at this time, especially students of the Midwifery Academy (AKBID) Al Baeti tahirah which is the gateway to health for the surrounding community. Objective: To find out the knowledge and attitudes of students of level I and II about HIV and AIDS in AKBID Tahirah Al Baeti Bulukumba Method: This type of research uses descriptive research. The number of samples used was 44 respondents. The sampling technique uses accidental sampling by using a questionnaire as a research instrument. Results: Based on data obtained from a questionnaire distributed to level I and II AKBID students Tahirah Al Baeti Bulukumba showed that students with sufficient knowledge about HIV and AIDS were 59.1% while the attitudes shown by students were sufficient by 50.0%. Conclusion: Knowledge and attitudes possessed by Tahirah Al Baeti Bulukumba Academy of Midwifery students on HIV and AIDS are in the sufficient category.